AB0329 Do anxious or depressive rheumatoid arthritis patients on biotechnologic therapy have worse disease activity, function and quality of life?. (15th June 2017) - Borges, J; Madeira, N; Cardoso, A; Cunha-Miranda, L; Barcelos, F; Miguel, C; Silva, C; Fernandes, S; Trinca, R; Medeiros, D; Campanilho-Marques, R; Santos, H; et al.
Abstract : Background: Depression, anxiety and fatigue are common symptoms in rheumatoid arthritis (RA) patients, and seem to influence disease activity, pain, quality of life (QoL) and treatment response. Objectives: To assess disease activity, function and QoL in RA patients with symptoms of anxiety/depression. Methods: Observational, cross-sectional study including RA patients on bDMARD followed at our centre, registered at Reuma.pt with ≥1 evaluation from 2015/11 to 2016/07. Clinical data including DAS28, CDAI, SDAI, TJC, SJC, patients' and physicians' pain/global assessments (VAS), ESR, CRP, HAQ, EQ5D, HADS score (anxiety and depression domains, cutoff ≥8) and FACIT-F were collected. Data were analyzed using Mann-Whitney, Qui-Squared and Spearman correlation, p<0.05. Results: 182 patients enrolled, 84.6% female, mean: age at 1st bDMARD 53.8±11.1; time since diagnosis 16.2±9.3 years; DAS28 3.54±1.3; CDAI 10.2±9.6; SDAI 11.2±10.4; HAQ 0.97±0.6; HADS-Anxiety 7.13±4.5; HADS-Depression 6.62±4.54, FACIT-F 35.1±9.2, EQ-5D 0.36±0.2. 77 (44.5%) patients scored ≥8 in the HADS-Anxiety domain and 71 (41.0%) scored ≥8 in the HADS-Depression domain. Comparison of depressive vs non-depressive and anxious vs non-anxious groups appears on table 1 . There was a correlation of HADS-Anxiety with DAS28 (r=0.391, p<0.001), CDAI (r=0.441, p<0.001), SDAI (r=0.426, p<0.001), HAQ (r=0.509, p<0.001), FACIT-F (r=-0.669, p<0.001) and EQ5D (r=-0.592, p<0.001). There was a correlation of HADS-Depression with DAS28 (r=0.389, p<0.001), CDAI (r=0.455, p<0.001), SDAI (r=0.439, p<0.001), HAQ (0.596, p<0.001), FACIT-F (r=-0.679, p<0.001) and EQ5D (r=-0.659, p<0.001). Conclusions: Anxious or depressive patients showed higher disease activity, especially in measures with some subjectivity (such as TJC and PGA) but not regarding ESR or CRP and worse function and QoL. This fact must be taken into account when evaluating therapeutic efficacy. Disclosure of Interest: None declared